2018
DOI: 10.1101/308247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The HCP 7T Retinotopy Dataset: Description and pRF Analysis

Abstract: About a quarter of human cerebral cortex is tiled with maps of the visual field. These maps can be 3 measured with functional magnetic resonance imaging (fMRI) while subjects view spatially modulated 4 visual stimuli, also known as 'retinotopic mapping'. One of the datasets collected by the Human 5Connectome Project (HCP) involved ultra-high-field (7 Tesla) fMRI retinotopic mapping in 181 healthy 6 adults (1.6-mm resolution), yielding the largest freely available collection of retinotopy data. Here, we 7 descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 81 publications
2
17
0
Order By: Relevance
“…The increase in temporal window length was systematic but small, increasing by about 30% from V1 to the anterior maps just beyond V3. Qualitatively, this is similar to the increase in spatial receptive field size across the cortical hierarchy, but the differences in spatial receptive fields are larger: receptive field size more than doubles from V1 to V3, and increases by at least 4 times from V1 to V4, measured with either single units (32)(33)(34)(35) or fMRI (20,36,37). Other studies have also found a hierarchy of temporal processing human and macaque cortex.…”
Section: Temporal Window Lengthsupporting
confidence: 67%
“…The increase in temporal window length was systematic but small, increasing by about 30% from V1 to the anterior maps just beyond V3. Qualitatively, this is similar to the increase in spatial receptive field size across the cortical hierarchy, but the differences in spatial receptive fields are larger: receptive field size more than doubles from V1 to V3, and increases by at least 4 times from V1 to V4, measured with either single units (32)(33)(34)(35) or fMRI (20,36,37). Other studies have also found a hierarchy of temporal processing human and macaque cortex.…”
Section: Temporal Window Lengthsupporting
confidence: 67%
“…The prior map, used for methods 2 and 3, was derived from fitting a template to a high-quality dataset derived from 181 subjects in the Human Connectome Project [37][38][39].…”
Section: !mentioning
confidence: 99%
“…individual brains. Our new method, combined with large datasets such as the HCP retinotopy data set [39], could be used to address this question.…”
Section: S1203 Lh Datasetmentioning
confidence: 99%
See 2 more Smart Citations